2016
DOI: 10.1021/acs.jpca.6b08062
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Metalloporphyrin–Oligomer Multianions: Cofacial versus Coplanar Motifs as Resolved by Ion Mobility Spectrometry

Abstract: ABSTRACT:We have combined ion mobility mass spectrometry with quantum chemical calculations to investigate the gasphase structures of multiply negatively charged oligomers of mesotetra(4-sulfonatophenyl)metalloporphyrins comprising the divalent metal centers Zn II , Cu II , and Pd II . Sets of candidate structures were obtained by geometry optimizations based on calculations at both the semiempirical PM7 and density functional theory (DFT) levels. The corresponding theoretical cross sections were calculated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Finally, we compared its calculated CCS with the measured CCS. The structures of noncovalently linked TPP dimers are published [38] . We thus determined a scaling factor of 0.94.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we compared its calculated CCS with the measured CCS. The structures of noncovalently linked TPP dimers are published [38] . We thus determined a scaling factor of 0.94.…”
Section: Resultsmentioning
confidence: 99%
“…Porphyrins have been studied in the gas phase using mass 6 and ion mobility 7,8 spectrometry, as well as infrared, 9 photodissociation 10 and photoelectron spectroscopy. [11][12][13][14] Protoporphyrin IX is a D 2h porphyrin with two propionic acid groups as substituents on the macrocycle, which can form a carboxylate monoanion or dicarboxylate dianion following the removal of one or two protons.…”
Section: Introductionmentioning
confidence: 99%
“…The observed changes in Ω exp were compared to Ω calc values obtained from trajectory method applied to carefully optimised DFT structures. This built on similar earlier work observing the change in oligomeric metalloporphyrin geometry as the coordinating metal was changed ( Brendle et al, 2016 ). It was found that for M II containing oligomers, the charge state of the oligomer, and the corresponding number of sodium counterions, dictated if the structure formed would be “open” or “closed.” Interestingly, M III containing oligomers did not exhibit the same pattern, as the sulfonic groups of the porphyrins could readily bind to the central metals.…”
Section: Applications Of Ion Mobility Mass Spectrometry To Study Coordination Driven Self-assemblymentioning
confidence: 77%